Preoperative echocardiography as a prognostic tool for liver transplant in patients with hypertrophic cardiomyopathy. Issue 2 (29th November 2021) - Pai, Sher‐Lu; Chadha, Ryan M.; Logvinov, Ilana I.; Brigham, Tara J.; Watt, Kymberly D.; Li, Zhuo; Palmer, William C.; Blackshear, Joseph L.; Aniskevich, Stephen
Abstract: Background: Hypertrophic cardiomyopathy (HCM) presents with a hypertrophied left ventricle (LV). It is often associated with LV outflow tract obstruction (LVOTO) and a risk for sudden death. This study aimed to describe outcomes of patients with HCM who underwent liver transplant (LT). Methods: A retrospective review was conducted for patients diagnosed with HCM undergoing LT. Patient characteristics, preoperative echocardiography results, HCM risk of sudden cardiac death prediction model score, and 5‐year mortality were examined. A univariable Cox proportional hazards model was used to evaluate the association between risk factors and 5‐year mortality. All tests were two‐sided with the alpha level set at .05. Results: Twenty‐nine patients were included in the analysis. Six patients (21%) had a perioperative cardiopulmonary complication. The 5‐year survival rate was 61% (95% CI, 45–82). The analyzed risk factors showed that 5‐year post‐LT survival was significantly predicted by maximal LV outflow tract gradient at rest > 60 mmHg (hazard ratio, 1.04 [95% CI, 1.01‐1.06]). Conclusions: Preoperative LV outflow tract resting gradient > 60 mmHg was associated with 5‐year post‐LT mortality. The results suggest the severity of LVOTO identified by echocardiography is a prognostic tool for patients with HCM after LT.